Report on proposed new interior design scheme of Harley Davidson’s Clubhouse for Naza Prestige Bikers Sdn. Bhd. at Jalan Pekeliling Tasek, 31400 Ipoh, Perak / Muhammad Nasreen Zulimi - Zulimi, Muhammad Nasreen (Faculty of Architecture, Planning and Surveying, 2011)
Project report is one of the vital subject that every semester 06 Diploma of Interior Design or final year in order to graduate. The objective of the report is to give student an oppurtunity to understand spatial design studies through drawings and plan language. The subject requires students to conduct researches based on their semester 06. This project report is on proposing a new design scheme of Harley Davidson’s Clubhouse for NAZA Prestige Bikers at Jalan Pekeliling, 31400 Ipoh, Perak. Internet is one of the source for information in this study. Other than that, interviews with one of the general manager in NAZA prestige Bikers also proves fruitful in the research. This clubhouse serves as a service center and lounges for Harley Davidson aficionados or what we call as HOGs in acronym of Harley Owners Group. In addition, the clubhouse also serves as sales and event place. This clubhouse also as a stepping stone for NAZA in order to widen the Harley Davidson business opportunity in Perak. In this paper we describe the meaning of clubhouse, services, space requirement at academy and many more . The focus is to design a clubhouse that is functional, attractive and according to the biker’s interests.